Ni(ii)-catalyzed C–H hydroarylation of diarylacetylenes with imidazolium salts. Issue 16 (3rd February 2022) - Wang, Tianbao; Zheng, Xuesong; Zheng, Qinze; Zhou, Fulin; Wang, Linhua; Gao, Ge
Abstract : A Ni(ii )-catalyzed C–H hydroarylation of diarylacetylenes with imidazolium salts without adding any ligand was developed. It provides an easy and efficient access to ( E )-2-(1, 2-diarylvinyl)imidazolium salts. Abstract : A simple Ni(ii )-catalyzed C–H hydroarylation of diarylacetylenes with imidazolium salts without adding any ligand was developed. It provides a facile and efficient access to ( E )-2-(1, 2-diarylvinyl)imidazolium salts. The preliminary results indicate a rare nonredox catalytic cycle of Ni(ii ), complementary to the common redox catalytic cycle starting from Ni(0).